Implementación de un sistema de gestión y mantenimiento programado de equipos tecnológicos e industriales, aplicando la metodología scrum, para el departamento de mantenimiento de la planta ensambladora ciauto, en la ciudad de Ambato, durante el periodo 2014 - 2015 - Gutiérrez Jácome, Darío (2016)
In this project the development and implementation of the management system and scheduled maintenance of technological and industrial equipment are detailed, which was developed for the maintenance department of the detailed CIAUTO assembly plant. The system will help to keep track of digital formats such as documents, records, plans and instructions that allow the name of the control processes of planning activities in the maintenance department. It has been found that industrial computers can be monitored regularly, and minimize failures in several ways, with the use of a PostgreSQL database and Java programming language to be tools for SCRUM methodology, the same methodology of agile software development allows the project to add new functional requirements in each interaction; for the access to the system, a username and password for each department is used, the user can access to all ROOT system modules; the system is divided into two modules: Module maintenance and module systems, the modules are independent….